Structural and rheological properties of nonedible vegetable oil-based resin - Mudri, Nurul Huda; Abdullah, Luqman Chuah; Min, Min Aung; Awang Biak, Dayang Radiah; Tajau, Rida (MDPI AG, 2021)
Jatropha oil-based polyol (JOL) was prepared from crude Jatropha oil via an epoxidation and hydroxylation reaction. During the isocyanation step, two different types of diisocyanates; 2,4-toluene diisocyanate (2,4-TDI) and isophorone diisocyanate (IPDI), were introduced to produce Jatropha oil-based polyurethane acrylates (JPUA). The products were named JPUA-TDI and JPUA-IPDI, respectively. The success of the stepwise reactions of the resins was confirmed using 1H nuclear magnetic resonance (NMR) spectroscopy to support the Fourier-transform infrared (FTIR) spectroscopy analysis that was reported in the previous study. For JPUA-TDI, the presence of a signal at 7.94 ppm evidenced the possible side reactions between urethane linkages with secondary amine that resulted in an aryl-urea group (Ar-NH-COO-). Meanwhile, the peak of 2.89 ppm was assigned to the α-position of methylene to the carbamate (-CH2NHCOO) group in the JPUA-IPDI. From the rheological study, JO and JPUA-IPDI in pure form were classified as Newtonian fluids, while JPUA-TDI showed non-Newtonian behaviour with pseudoplastic or shear thinning behaviour at room temperature. At elevated temperatures, the JO, JPUA-IPDI mixture and JPUA-TDI mixture exhibited reductions in viscosity and shear stress as the shear rate increased. The JO and JPUA-IPDI mixture maintained Newtonian fluid behaviour at all temperature ranges. Meanwhile, the JPUA-TDI mixture showed shear thickening at 25 °C and shear thinning at 40 °C, 60 °C and 80 °C. The master curve graph based on the shear rate for the JO, JPUA-TDI mixture and JPUA-IPDI mixture at 25 °C, 40 °C, 60 °C and 80 °C was developed as a fluid behaviour reference for future storage and processing conditions during the encapsulation process. The encapsulation process can be conducted to fabricate a self-healing coating based on a microcapsule triggered either by air or ultra-violet (UV) radiation.